Marginal land bioethanol production of sweet sorghum based on limited water resources in Northwest China - Shi, Xinjie; Du, Taisheng; Dong, Pingguo; Hu, Tiemin (International Journal of Agricultural and Biological Engineering, 2022)
Sweet sorghum is considered a leading non-grain candidate for bioethanol production due to its low input requirement, good tolerance, high biomass potential, and high sugar content. However, insufficient studies have been conducted on the spatial distribution of sweet sorghum-based bioethanol production potential considering the water resources limitation. We presented a multi-factor analysis method not only considering terrain, meteorology, soil, and crop natural growth habits but also considering the local water resource to explore the available marginal land suitable for sweet sorghum cultivation and assess the bioethanol production potential in Northwest China. The results showed that 4.63×107 hm2 available marginal land was suitable for sweet sorghum planting. Considering the constraint of local water resources, 2.76×106 hm2 available marginal land was suitable for sweet sorghum planting, accounting for 4.7% of the total available marginal land. And 1.23×1010 L bioethanol could be produced on it. Moreover, for these districts under low water stress levels, 9.79×105 hm2 available marginal land in Gannan Tibet AP and Longnan of Gansu and Hulun Buir of Inner Mongolia was considered a priority to develop sweet sorghum-based bioethanol, and 5.56×109 L bioethanol could be produced in these districts, which can satisfy the 1.54% biofuel goal for 2050 of China. Keywords: bioethanol potential, marginal land, sweet sorghum, regional water stress levels, water resources limitation DOI: 10.25165/j.ijabe.20221503.6122 Citation: Shi X J, Du T S, Dong P G, Hu T M. Marginal land bioethanol production of sweet sorghum based on limited water resources in Northwest China. Int J Agric & Biol Eng, 2022; 15(3): 132–138.